Hole-mediated ferromagnetic enhancement and stability in Cu-doped ZnOS alloy thin films - Li, Y. F. (2013)
We report room temperature ferromagnetism enhancement of Cu-doped ZnOS (Zn1−xCuxO1−ySy) alloy thin films with high hole concentration. The Zn0.91Cu0.09O0.92S0.08 alloy thin films with a hole concentration of 4.3 × 1019 cm−3 show the strongest magnetization of 1.5μB/Cu. First-principles calculation shows that high hole concentration stabilizes the ferromagnetic ordering in the Zn1−xCuxO1−ySy system, indicating a strong correlation between ferromagnetic stability and hole concentration. These results suggest that the Zn1−xCuxO1−ySy alloy with high hole concentration is promising to find applications in spintronic devices.